Structure and functions of glutathione transferases - O. M. Fedets (The Ukrainian Biochemical Journal, 2014)
Data about classification, nomenclature, structure, substrate specificity and role of many glutathione transferase’s isoenzymes in cell functions have been summarised. The enzyme has been discovered more than 50 years ago. This family of proteins is updated continuously. It has very different composition and will have demand for system analysis for many years.